Procognitive Effects of Hexane Extracts of Michelia Champaca Leaves in Normal and Memory Deficit Mice - Ahmad, Hafsa; Saxena, Vasundhara; Mishra, Anurag; Gupta, Rajiv; Saraf, Shubhini A (Pharmacognosy Communications)
Introduction: Michelia champaca (Magnoliaceae), commonly known as Svarna champa is a glorious ancient Indian medicinal plant, rich in flavonoids and possessing several folkloric uses, traditionally claimed of having CNS effects. This study was undertaken to ascertain the nootropic potential (memory enhancing effects) of the hexane extracts of the leaves of Michelia champaca (Magnoliaceae) using rectangular maze and Y maze (interoceptive behavioral models). Methods: Hexane extracts of leaves of Michelia champaca (dosed at 100 and 200 mg/kg each) were administered to adult Swiss albino Wistar mice and the effect on acquisition, retention and retrieval of spatial recognition memory was determined, by using rectangular maze and Y maze (interoceptive behavioral models). Bacopa monniera extract was used as the standard drug while Scopolamine hydrobromide served as the amnestic agent. Results: The higher doses of the Michelia champaca extract exhibited a more promising nootropic potential. Maximal response was observed in the 200 mg/kg dose of extract, which closely approximated the results for the standard drug Brahmi. The higher dose elicited greater responses in both the models studied and were comparable to that achieved with the standard drug. Conclusion: The hexane extract of Michelia champaca afforded mild memory enhancing effects, the higher dose evoking pronounced alteration of behavior and better learning assessments.
Keywords: Michelia champaca; memory enhancing; cognitive; HPTLC; Quercetin